2008
DOI: 10.2298/apt0839181p
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-activity relationships to predict antibacterial effect of some benzimidazole derivatives

Abstract: The antibacterial activity of some substituted benzimidazole derivatives against Gram negative bacteria Escherichia coli was investigated. The tested compounds displayed in vitro inhibitory activity and their minimum inhibitory concentrations were determined. Quantitative structure-activity relationship has been used to study the relationships between the antibacterial activity and lipophilicity parameter, logP. Lipophilicity parameters were calculated for each molecule by using CS Chem-Office Software version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The structures of benzimidazole derivatives (n = 42) included in the study were selected from the literature. Compounds bearing 2-aminobenzimidazole (1-3) and hydrazone moieties (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were presented in the study by Özkay et al 2011 (14). They reported that synthesized novel benzimidazole-hydrazone exhibited low antibacterial activity, while in contrast the compound showed significant antifungal activity against Candida yeasts.…”
Section: Data Sources For In Silico Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The structures of benzimidazole derivatives (n = 42) included in the study were selected from the literature. Compounds bearing 2-aminobenzimidazole (1-3) and hydrazone moieties (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) were presented in the study by Özkay et al 2011 (14). They reported that synthesized novel benzimidazole-hydrazone exhibited low antibacterial activity, while in contrast the compound showed significant antifungal activity against Candida yeasts.…”
Section: Data Sources For In Silico Assessmentmentioning
confidence: 99%
“…The group of thiazolobenzimidazolones did not express their antibacterial activity against tested strains. 2-Methylbenzimidazole (29), 1-substituted-2-methylbenzimidazoles (30-35), 2-aminobenzimidazole (36) and 1-substituted-2-aminobenzimidazoles (37-42) were previously reported to express effective antifungal activity against Saccharomyces cerevisiae (6).…”
Section: Data Sources For In Silico Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One method that has been extensively employed involves the QSAR approach together with multivariate data analysis, combined with statistical design (Vasanthanathan et al, 2006). This approach is an attempt to show that there is a relationship between biological activities of compounds and structural or molecular descriptors such as physicochemical, thermodynamic, electronic, topological or geometrical parameters (Podunavac-Kuzmanović et al, 2008). The importance of the lipophilic or hydrophobic nature of bioactive compounds has been brought into fore by the tremendous progress in the use of QSAR methods.…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%
“…Several thousands of benzimidazole analogs have been synthesized and screened for their antimicrobial activity up-to-date (Podunavac-Kuzmanovic et al, 2008). The cause of a special notice on benzimidazole compounds has been cyanocobalamine (vitamin B 12 ) which bears 5,6-dimethylbenzimidazole fragment and is capable of inducing the growth of bacteria.…”
Section: Introductionmentioning
confidence: 99%